The Effect of Work Discipline and Work Environment on Motivation and Its Impact on Employee Performance (A Study at the Road Project Management Unit, Ministry of Public Works, Dili, Timor Leste) - Fernandes, Amaro Bino Da Costa (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Employee performance is one of the main indicators in measuring the success of an organization, including in the government sector which demands efficiency, accountability, and optimal public service. Good performance is not only influenced by technical capabilities, but also by internal organizational factors such as work discipline, work environment, and motivation. This study aims to empirically analyze: (1) the effect of work discipline on motivation and performance; (2) the effect of work environment on motivation and performance; and (3) the role of motivation as a mediating variable between work discipline and work environment on employee performance in the Road Project Management Unit (PMU), Ministry of Public Works, Timor-Leste. This study uses a quantitative approach with a causal associative design. The number of respondents was 40 employees of the ROAD PROJECT MANAGEMENT UNIT (PMU). The data collection technique was carried out by distributing closed questionnaires using a Likert scale. Data analysis was carried out through path analysis with the help of SPSS version 23.0, and the mediation test was carried out with the Sobel Test to test the indirect effect. The results of the study showed that, (1) Work discipline has a positive and significant effect on motivation, but does not have a direct effect on performance. (2) The work environment has a positive and significant effect on both motivation and performance directly. (3) Motivation plays a significant role in mediating the relationship between work discipline and performance, but does not mediate the relationship between work environment and performance. The practical implications of these findings indicate that efforts to increase employee motivation through discipline enforcement and the creation of a conducive work environment are strategic steps to encourage increased employee performance. This study is expected to be a reference for the development of human resource management policies in government institutions in Timor-Leste.